What Determines the Probability of Discovering a Species? A Study of the Completeness of Bryophyte Inventories in Tianmushan National Nature Reserve (Zhejiang, China) - Xue Yao; Zun Dai; Yiran Wang; Jian Zhang; Jian Wang (Ecology and Evolution)
ABSTRACT Knowing the total number of species in a region has been a question of great interest motivated by the need to provide a reference point for current and future losses of biodiversity. Unfortunately, obtaining an accurate number is constrained by the fact that most species remain to be discovered, due to the imperfect detection of species in the field collection or because of temporal turnover in species composition. Here, to understand the inventory completeness at the local scale, we studied the temporal dynamics in the species richness and composition of bryophytes in Tianmushan National Nature Reserve. We used β‐diversity to measure the temporal variation and analyzed the species attributes of newly discovered species collected this time. Furthermore, we evaluated our sampling strategy to measure sampling effect and estimated the species that remain to be discovered. We found that total β‐diversity was largely driven by turnover. The analysis of species attributes showed that epiphytic species dominate the newly recorded species in both the narrow and wide elevational range species. Further, if only one of the methods was adopted, 26%–29% of the newly discovered species would be missed, and we inferred that there are likely are 185 bryophytes yet to be discovered. Our results indicate that when the same effort was made, an appropriate sampling methodology is crucial to accelerate newly recorded species discovery. Further, the results of our study highlight that species temporal turnover should be considered when assessing the completeness of species inventories at the local scale.